Speech-evoked neurophysiologic responses in children with learning problems: development and behavioral correlates of perception. - Cunningham J; Nicol T; Zecker S; Kraus N; Cunningham, J; Nicol, T; Zecker, S; Kraus, N (Ear & Hearing (01960202), 2000)
Objectives: To evaluate the maturational progression of speech-evoked P1/N1/N2 cortical responses over the life span, determine whether responses are distinctive in clinical populations experiencing learning problems and elucidate the functional significance of these responses.Design: The P1/N1/N2 complex was measured in 150 normal subjects (5 to 78 yr) and 86 subjects with learning problems (LP) (8 to 15 yr) to a synthetic CV syllable. Analyses included description and comparison of the developmental time course in both groups and evaluation of the relationship between P1/N1/N2 and children's performance on speech discrimination tasks and standardized learning measures.Results: Findings revealed significant changes in waveform morphology, latency and amplitude as a function of age. Maturational patterns in the group of children with learning problems did not differ from the normal group. P1/N1/N2 parameters were significantly correlated with standardized tests of Spelling, Auditory Processing and Listening Comprehension in the LP group. Moreover, there was a predictive relationship between Auditory Processing and N2 latency.Conclusions: The P1/N1/N2 complex changes throughout life from school-age to old age. The developmental sequence throughout the school-age years is similar in normal and LP children. Thus, differences in the rate of P1/Nl/N2 latency and amplitude development do not appear to be distinctive in these two populations. The relationship between P1/N1/N2 parameters and standardized measures of learning (particularly between Auditory Processing and N2 latency) provides new information about the role of these responses in hearing and highlights the potential value in characterizing auditory processing deficits.